El despido intempestivo en el código de trabajo para el sector privado y su vulneración al derecho a la estabilidad laboral - Zambrano Rivera, Linda Keila (2020)
The untimely dismissal in the Labor Code for the private sector and its violation of the right to job stability, as it is considered a current problem, whose antecedents are found in the contradiction between articles 33; 325 of the Constitution of the Republic, and Article 188 of the Labor Code, which raises work as a right, social duty, source and basis of the family economy, arguing that the State will guarantee this right to work, which will protect the worker; with the exception of said rules and principles, with financial compensation that compensates the worker for the unilateral termination of the employment relationship. The investigation is directed towards a mixed, descriptive, documentary and historical study through an extensive bibliographic review, the application of surveys and interviews to determine legal causes and consequences of untimely dismissal, concluding with a reform project, to article 188 of the Labor Code, to establish a new scale of compensation more in line with the economic reality of the country and seek to compensate for this violated right………..